A novel autotrophic denitrification and nitrification integrated constructed wetland process for marine aquaculture wastewater treatment. (April 2023) - Zhao, Lin; Fu, Guiping; Pang, Weicheng; Li, Xiaxin; Pan, Chao; Hu, Zhangli
Abstract: We undertook a lab-scale evaluation of a novel autotrophic denitrification and nitrification integrated constructed wetland (ADNI-CW) for improved carbon (C), nitrogen (N), and sulfur (S) cycling to treat mariculture wastewater. The process involved an up-flow autotrophic denitrification constructed wetland unit (AD-CW) for sulfate reduction and autotrophic denitrification, and an autotrophic nitrification constructed wetland unit (AN-CW) for nitrification. The 400-day experiment investigated the performance of the AD-CW, AN-CW, and entire ADNI-CW processes under various hydraulic retention times (HRTs), nitrate concentrations, dissolved oxygen levels, and recirculation ratios. Under various HRTs, the AN-CW achieved a nitrification performance exceeding 92%. Correlation analysis of the chemical oxygen demand (COD) revealed that, on average, approximately 96% of COD was removed by sulfate reduction. Under different HRTs, increases in influent NO3 − –N concentrations caused the amount of sulfide to gradually decrease from sufficient to deficient, and the autotrophic denitrification rate also decreased from 62.18 to 40.93%. In addition, when the NO3 − –N load rate was above 21.53 g N/m 2 ·d, the transformation of organic N by mangrove roots may have increased NO3 − –N in the top effluent of the AD-CW. The coupling of N and S metabolic processes mediated by various functional microorganisms ( Proteobacteria, Chloroflexi, Actinobacteria, Bacteroidetes, and unclassified_d__Bacteria ) enhanced N removal. We intensively explored the effects of changing inputs as culture species developed on the physical, chemical, and microbial changes of CW to ensure a consistent and effective management of C, N, and S. This study lays the foundation for green and sustainable mariculture development. Graphical abstract: Image 1 Highlights: Under various HRTs, AN-CW can achieve more than 92% nitrification performance. C and N were mainly removed by sulfate reduction and autotrophic denitrification. The root exudates of Kandelia candel limited the nitrogen removal of ANDI-CW system. We provide insights into the C, N, and S cycles in the CW treatment process. ANDI-CW process provides a promising way for the treatment of mariculture wastewater.